Multi-omics analysis of gut microbiota and metabolites reveals contrasting profiles in domestic pigs and wild boars across urban environments - Ding, Jingjing; Cui, Xinyuan; Wang, Xuan; Zhai, Feifei; Wang, Lei; Zhu, Lifeng (Frontiers in Microbiology, 2024)
The gut microbiota plays a crucial role in host health and metabolism. This study explores the differences in gut microbiota and metabolites between domestic pigs (DP) and wild boars (WB) in urban environments. We analyzed gut microbial composition, metabolic profiles, virome composition, antibiotic resistance genes (ARGs), and human pathogenic bacteria (HPB) in both DP and WB. Our results revealed that DP exhibited a higher Firmicutes/Bacteroidetes ratio and were enriched in bacterial genera associated with domestication and modern feeding practices. Metabolomic analysis showed distinct profiles, with WB significantly enriched in the Pantothenate and CoA biosynthesis pathway, highlighting dietary and environmental influences on host metabolism. Additionally, DP had a distinct gut virome composition, particularly enriched in lytic phages of the Chaseviridae family. ARG analysis indicated a higher abundance of tetracycline resistance genes in DP, likely due to antibiotic use in pig farms. Furthermore, variations in HPB composition underscored potential health risks associated with contact with pig feces. These findings provide valuable insights into the microbial ecology of domestic pigs and wild boars, emphasizing the importance of these comparisons in identifying zoonotic pathogen transmission pathways and managing antibiotic resistance. Continued research in this area is essential for developing effective strategies to mitigate public health risks and promote sustainable livestock management practices.